Microscopic flow mechanism considering the mechanical response on massive energy replenishment in tight oil reservoirs - Zhuoying Dou; Zhengming Yang; Changchun Dong; Haibo Li; Yimeng Wang; Chenyu Han; Huan Meng (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Highlights 1. Microscopic flow models are established considering the mechanical response in massive flooding and massive soaking. 2. The influence characteristics of the factors affecting massive energy replenishment are quantitatively revealed. 3. The differences of microscopic flow mechanism are compared in conventional and massive energy replenishment.